2010
DOI: 10.1128/jvi.00668-10
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A)-Binding Protein 1 Partially Relocalizes to the Nucleus during Herpes Simplex Virus Type 1 Infection in an ICP27-Independent Manner and Does Not Inhibit Virus Replication

Abstract: Infection of cells by herpes simplex virus type 1 (HSV-1) triggers host cell shutoff whereby mRNAs are degraded and cellular protein synthesis is diminished. However, virus protein translation continues because the translational apparatus in HSV-infected cells is maintained in an active state. Surprisingly, poly(A)-binding protein 1 (PABP1), a predominantly cytoplasmic protein that is required for efficient translation initiation, is partially relocated to the nucleus during HSV-1 infection. This relocalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 58 publications
(76 reference statements)
5
57
0
Order By: Relevance
“…It did, and additionally, transcription inhibition in the absence of infection led to PABP1 relocalization. We noted a more robust relocalization in cells that were both infected with RVFV MP12rLuc and treated with actinomycin D. As various cell stressors have been shown to lead to PABP1 relocalization, it is possible that factors related to the stress of infection also contribute to relocalization of PABP1 (41,61,62). We concluded that PABP1 relocalization is likely secondary to the NSs host transcription block.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It did, and additionally, transcription inhibition in the absence of infection led to PABP1 relocalization. We noted a more robust relocalization in cells that were both infected with RVFV MP12rLuc and treated with actinomycin D. As various cell stressors have been shown to lead to PABP1 relocalization, it is possible that factors related to the stress of infection also contribute to relocalization of PABP1 (41,61,62). We concluded that PABP1 relocalization is likely secondary to the NSs host transcription block.…”
Section: Discussionmentioning
confidence: 64%
“…Herpes simplex virus (HSV) proteins ICP27 and UL47 both bind to PABP1, leading to a decrease in PABP1's interaction with binding partners eIF4G and PABP-interacting protein 2 (40). Additionally, PABP1 partially relocalizes to the nucleus during HSV-1 infection (40,41). Rotavirus protein NSP3A functionally replaces and evicts PABP1 from the eIF4F complex and leads to nuclear relocalization of PABP1 (42,43).…”
mentioning
confidence: 99%
“…Thus, ICP27 may function in this capacity by targeting small subunit recruitment via PABP-eIF4G to promote the translation of specific viral mRNAs, two of which (VP16 and ICP5) have been identified to date. Intriguingly, PABP is relocalized to the nucleus in an ICP27-independent manner at late times postinfection (10,11), suggesting that ICP27 may provide a means to direct limiting amounts of cytoplasmic PABP to a subset of viral mRNAs late in infection (7,8). Moreover, because PABP nuclear export is largely mRNA-driven in mammalian cells (12), and ICP27 promotes export of viral mRNAs (17), it is possible that the ICP27-PABP interaction may allow nuclear-retained PABP to be recruited and exported on these mRNAs, enabling their efficient translation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cellular expression of PABPC is altered upon infection by members of all herpesvirus subfamilies. The alphaherpesvirus HSV causes nuclear accumulation of PABPC in infected cells (11,45), similar to the gammaherpesviruses. PABPC relocalization by HSV, however, occurs as a consequence of the combined expression of both ICP27, inhibiting mRNA splicing, and the vhs protein (11,31).…”
Section: Discussionmentioning
confidence: 99%